2016
DOI: 10.1017/s1041610216002076
|View full text |Cite
|
Sign up to set email alerts
|

The role of depression in the insomnia of people with subjective memory impairment, mild cognitive impairment, and dementia in a community sample of elderly individuals in South Korea

Abstract: Insomnia is a very common complaint in the elderly with SMI, MCI, and dementia. Depression might play an important factor in the relationship between insomnia and cognitive dysfunctional status in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Chronic insomnia induced by anxiety and depression is associated with memory impairment, dementia and inattention, including impaired alerting behaviour, orienting and executive control. [38][39][40] Similarly, OSA-related chronic intermittent hypoxia and hypercapnia can also hinder attention, memory and cognition. 41,42 Specifically, how SPD generates cognitive and behavioural dysfunction is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic insomnia induced by anxiety and depression is associated with memory impairment, dementia and inattention, including impaired alerting behaviour, orienting and executive control. [38][39][40] Similarly, OSA-related chronic intermittent hypoxia and hypercapnia can also hinder attention, memory and cognition. 41,42 Specifically, how SPD generates cognitive and behavioural dysfunction is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the SMC was assessed only based on the 10th question of the SGDS‐K. Kim et al 25 . defined SMC in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the effects of depression should be considered 23 . It has been reported that SMC is mainly a product of depressive symptoms and is weakly related to objective dysfunction 1, 24–26 . Third, the confounding effect of demographic variables that may affect SMC should be noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of elderly insomnia in China is 47.2% (5) and 57% in America (6). Insomnia severely affects the physical health and life quality of the elderly (7)(8)(9)(10)(11) and increases social and economic burden (6).…”
Section: Introductionmentioning
confidence: 99%